Politics, Power, and the Divine: The Rex Sacrorum and the Transition from Monarchy to Republic at Rome. (26th October 2017) - Glinister, Fay
Abstract: Whether the result of internal revolution or external factors, in the late sixth centuryBC Rome underwent regime change. A king, or at least a sole ruler of some sort, was replaced by a governmental system in which power was distributed amongst a wider aristocratic group. Just what that elite group comprised at that point in time remains open to question, and the institutional reality is certainly more complicated than the simple shift from monarchy to consulship portrayed in the later literary sources; 1 but as part of that change, according to Roman tradition, a priesthood was instituted to perform the deposed king's sacred duties. This priesthood provides us with an opportunity to reappraise the role of religion in the development of the Roman state, and a useful locus from which to assess changes in religious and political power in the transition from monarchy to Republic at Rome.